Syntactic Structure of English Multi-Words Verbs (Al-Farooq Journal of Sciences, 2026)
This paper examines the syntactic structure and classification of English multi-word verbs, which constitute an important and frequently used component of everyday English. It aims to clarify their formation, grammatical features, and major categories through a descriptive analysis supported by illustrative examples. The paper identifies three principal categories: phrasal verbs, consisting of a verb and an adverbial particle; prepositional verbs, formed by a verb and a preposition; and phrasal-prepositional verbs, comprising a verb, an adverbial particle, and a preposition. It further classifies phrasal verbs into transitive and intransitive types, while distinguishing separable from inseparable transitive constructions according to the position of the direct object. The analysis demonstrates that multi-word verbs function as unified syntactic and semantic units whose meanings may differ from those of their individual components. The paper concludes with representative examples of each category and their meanings.
Keywords: Multi-word verbs; Phrasal verbs; Prepositional verbs; Phrasal-prepositional verbs; Syntactic structure